Peran perilaku kerja terhadap promosi jabatan dan dampaknya pada kinerja pegawai Kementerian Agama Kota Jambi - Zikri, Ahmad; Rosita, Sry; Kurniawan, Dwi (Jurnal Dinamika Manajemen, 2019)
This study aims to examine the effect of work behavior on job promotion and its impact on employee performance at the Jambi City Ministry of Religion Office. The population in this study amounted to 100 employees at the Ministry of Religion of the Jambi City office, while the sample used in this study was 80 employees. This study uses quantitative methods. Data analysis was performed using the PLS (Partial Least Square) application. The dimensions of work behavior studied were Social Relations, Vocational Skills, Work Motivation, Self-Confidence Initiative. Dimensions of Position Promotion looked Opportunity for promotion: increased responsibilities, Increased duties, Added rights, Expanded authority. The dimensions of employee performance studied were work results, job knowledge, initiative, mental agility, attitude, punctuality, and absenteeism. The consequences of this study work behavior have a negative and insignificant effect on employee performance, work behavior has a positive and significant influence on a job promotion, job promotion has a positive and significant influence on employee performance, and work behavior on job promotion and its impact on employee performance has a positive and considerable effect.